2009
DOI: 10.1080/08927010902730516
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling activity of synthetic polymer gels against cyprids of the barnacle (Balanus amphitrite) in vitro

Abstract: Barnacle (Balanus amphitrite) settlement on synthetic hydrogels with various chemical structures was tested in laboratory assays. The results demonstrated that cyprids settle less or not at all on hydrogels and PDMS elastomer compared with the polystyrene control. The low settlement on gels is most likely due to the 'easy release' of initially attached cyprids from the gel surfaces. This low adhesion of cyprids is independent of surface hydrophilicity or hydrophobicity, and of surface charge. The results also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…We have recently found that when the charged gels are swelling in aqueous solutions with a high ionic strength, such as the HEPES buffer solution (ionic strength I=0.15) or sea water (I=0.7) [15],whereupon the osmotic swelling term of the dissociated counter-ions is screened, they also, approximately, obey the relation of E ~ q -3 of the neutral gel. Therefore, we can assume that the behaviors of the cells are also not correlated to the elastic modulus of the gels in the present case.…”
Section: Ec Adhesion Spreading and Proliferation On Various Kinds Omentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently found that when the charged gels are swelling in aqueous solutions with a high ionic strength, such as the HEPES buffer solution (ionic strength I=0.15) or sea water (I=0.7) [15],whereupon the osmotic swelling term of the dissociated counter-ions is screened, they also, approximately, obey the relation of E ~ q -3 of the neutral gel. Therefore, we can assume that the behaviors of the cells are also not correlated to the elastic modulus of the gels in the present case.…”
Section: Ec Adhesion Spreading and Proliferation On Various Kinds Omentioning
confidence: 99%
“…After sterilization by autoclaving (120˚C, 20 min), the gels disks (diameter is 15 seeded on the gel surfaces that not been modified by any cell-adhesive proteins or peptides before cell culture. The cell-loaded samples were cultured at 37C in a humidified atmosphere of 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…Such structures are reproduced as 3-dimensional patterned surfaces fabricated from synthetic polymers (e.g. Murosaki et al 2009, Aldred et al 2010bAhmed et al 2011;Greco et al 2013;del Campo 2013). Using such surfaces, Aldred et al (2010b) demonstrated similar effects on the settlement of cyprids of B. amphitrite as had been observed previously for B. improvisus.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the settling behaviour of fouling larvae during the initial stages of colonization as well as the innate criteria they use to discriminate between surfaces (Matsumura et al1998;Andersson et al 1999;Berntsson et al 2004;Murosaki et al 2009) will play an important role in the development of antifouling coatings. Barnacles are one of the most thoroughly studied groups of fouling organisms due to their significant economic impact and relative simplicity of rearing in the laboratory (Holm 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are soft and wet materials with many specific features such as solute permeability [1], low surface sliding friction [2,3], and antifouling properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%